Effect of production temperature on thermal and mechanical properties of polystyrene-fly ash composites - Bicer, Ayse (Sage Publications Ltd, 2020)
This study was conducted to produce a novel construction material by using two different types of waste material consisting of fly ash and fragmented polypropylene (PP). These two materials were mixed on various ratios, and samples with smooth surface were obtained by compressing with 50 kg of weight after each mixture is heated on temperatures of 225 degrees C, 250 degrees C, and 275 degrees C and poured into the molds. Thermal and mechanical tests were performed on the prepared samples. As a result, with the evaluation of two waste materials such as fly ash and PP, (i) the contamination caused by the waste materials will be prevented; (ii) as the fly ash rate increases, the thermal properties of samples produced under 225 degrees C of temperature will be enhanced; (iii) as the fly ash rate increases, the thermal properties of samples produced under 225 degrees C of temperature will be enhanced, and PP ratio and production temperature must be high in order to improve mechanical properties; (iv) the produced composite materials bear the low-cost heat, acoustics, and water insulation, while it will also be possible for the same to be used as coating materials on the walls and tiling in the buildings.
Keywords: fly ash; polypropylene; waste management; composite materials